2010
DOI: 10.2478/v10043-010-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle of Cryptomyzus Leonuri Bozhko, 1961 in Lithuania with the Description of previously unknown Morphs

Abstract: Cryptomyzus leonuri is the least investigated species of this genus in Europe. So far, the description of one morph, an apterous viviparous female, has been published (Bozhko 1961), and its life cycle remains unclear. This paper presents descriptions of previously unknown alate viviparous females, males and oviparous females of C. leonuri and the redescription of an apterous viviparous female, which has been also compared with the original description (Bozhko 1961) and character values indicated in the identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The present study confirmed that precise morphological discrimination between C. leonuri and C. alboapicalis remains a difficult task (Guldemond 1991;Bašilova 2010) and canonical functions are still needed for the proper morphological separation of these two species. In addition to the common key characters (SRHIN3, SIPHON/CAUDA, PT/BANT6), DHAS1-4, LRS and MAWSI were included for more precise morphological identification of C. alboapicalis and C. leonuri apterous viviparous females.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The present study confirmed that precise morphological discrimination between C. leonuri and C. alboapicalis remains a difficult task (Guldemond 1991;Bašilova 2010) and canonical functions are still needed for the proper morphological separation of these two species. In addition to the common key characters (SRHIN3, SIPHON/CAUDA, PT/BANT6), DHAS1-4, LRS and MAWSI were included for more precise morphological identification of C. alboapicalis and C. leonuri apterous viviparous females.…”
Section: Discussionsupporting
confidence: 83%
“…Characters for morphometric analysis (Table 2) were selected from the identification keys and morphological descriptions of both species (Hille Ris Lambers 1953;Bozhko 1961;Guldemond 1991;Heie 1994;Bašilova 2010). Measurements were performed with the Olympus BX40 microscope and the interactive measuring system MicroImage (OlympusOptical Co. GmbH).…”
Section: Morphometric Analysismentioning
confidence: 99%
See 2 more Smart Citations